PERTIMBANGAN PUTUSAN HAKIM DALAM PERKARA TINDAK PIDANA PENYEDIA JASA TELEKOMUNIKASI INTERNET WIFI ILEGAL (Studi Putusan Nomor 411/Pid.Sus/2021/Pn Pgp) - Setiyawan, Erlangga Bagus; Fadlian, Aryo (Jurnal Ilmiah Dinamika Hukum, 2024)
The In the current era, Internet Service Providers (ISPs), also known as Penyelenggara Jasa Telekomunikasi Layanan Akses Internet, are emerging rapidly, offering internet services at varying prices. However, the demand for high-speed internet is increasing while complex regulations create opportunities for misuse by individuals or specific groups. The purpose of this writing is to understand the implementation of criminal law, causal factors, and judicial considerations regarding the criminal acts of illegal WiFi internet service providers in Decision Number 411/Pid.Sus/2021/PN.Pgp. This study adopts a juridical-normative approach, aiming to examine positive legal regulations and utilizing legal materials as the primary data. The data sources consist of primary legal materials, such as legislation and judicial decisions, as well as secondary legal materials, including legal opinions, doctrines, legal theories from legal literature, research findings, scholarly articles, and relevant websites. The substantive implementation of criminal law in this case is in accordance with the elements specified in the relevant articles. Individual and external factors, such as the social environment, influence the occurrence of crimes. The judge's consideration to impose a lighter sentence than the Prosecutor's demand is based on mitigating factors, which outweigh the aggravating factors for the defendant. Keywords : Criminal Law, Judge's consideration, Telecommunication